PRAKTEK AKUNTANSI PENETAPAN NILAI BELIS PERKAWINAN SUKU LIO DESA BOKASAPE TIMUR, KECAMATAN WOLOWARU, KABUPATEN ENDE - Angelina Novita Nabo; Nikson Tameno; Siprianus G. Tefa (ICMA Nasional, 2025)
Abstract This study discusses accounting practice in determining the value of belis in the marriage customs of the Lio tribe in East Bokasape Village, Wolopuru District, Ende Regency. The goal is to identify, measure, and record the value of belis in the marriage customs of the Lio tribe in East Bokasape Village. The type of research used in this study is qualitative. The type of data used is qualitative data supported by quantitative data. Data collection was obtained from observation, interviews, documentation and literature studies using Miles and Huberman data analysis techniques and using Nvivo software application tools. This research focuses on accounting practice with three (3) stages, namely, identification, measurement, and record-keeping. The results of this study are in the form of accounting science recording which is carried out simply, so that the results are found to be related to the relationship of the accounting approach in giving belis to the marriage customs of the Lio Tribe of East Bokasape Village which is a material for information and consideration about belis in accounting, including: (1) identification in belis is said to be relevant because economic transactions can be identified as a source of measurement and recording in accounting. (2) The research shows that the process of measuring belis, measured using the fair value